ANALISIS KRITIK SASTRA PADA CERPEN ‘KETIKA HARAPAN TERTUMPU PADA ANAK PERTAMA’ KARYA PUTRI L SIHOMBING MENGGUNAKAN PENDEKATAN EKSPRESIF - Putri L. Sihombing (JURNAL ILMIAH NUSANTARA, 2026)
This study aims to analyze the literary criticism of the short story "When Hope Rests on the First Child" by Putri L. Sihombing using an expressive approach. This approach is used to uncover the relationship between the author's inner experiences, feelings, and outlook on life with the story structure constructed within the short story. This study employed a qualitative approach with a literary text analysis method. Data collection techniques were conducted through literature review and close reading of the text. Data analysis techniques included narrative analysis, text analysis, an expressive approach, and character study. The results show that this short story strongly represents the author's inner world through the character of "I" as the center of the narrative. The themes of parental expectations, the responsibility of the first child, economic limitations, and academic failure reflect the author's emotional experiences, expressed through conflict, dialogue, and an emotional and reflective style. Thus, this short story functions not only as a work of fiction but also as a medium for the author's inner expression of the social reality she experiences. The expressive approach proves relevant to understanding the short story's meaning as a whole by placing the author as the primary source of meaning formation.